PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Sari, Lupita Puspita; Syahzuni, Barlia Annis (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
This research seeks to examine the influence of capital structure, liquidity, and firm size on the valuation of pharmaceutical sub-sector companies and hospitals on the Indonesia Stock Exchange throughout the period spanning 2019 to 2022. The study utilizes independent variables, namely Debt to Equity Ratio (DER) representing capital structure, Current Ratio (CR) representing liquidity, and Size representing company size. The dependent variable, company value, is assessed using the Price to Book Value (PBV). The study encompasses a population of 23 companies, from which a purposive sample of 16 companies is selected over a four-year duration, resulting in a total of 64 research samples. Data analysis is conducted through multiple linear regression utilizing statistical software. The results suggest, collectively, capital structure, liquidity, and company size have an impact on company value. Specifically, the capital structure and liquidity variables demonstrate a partially significant positive influence on company value, whereas the company size variable does not exhibit a partially significant effect. The practical implication implies that companies should optimize their financing for operational needs, enabling investors to evaluate the company's value based on an optimal capital structure and its capacity to fulfill financial obligations